Food Bank Usage Is a Poor Indicator of Food Insecurity: Insights from Canada. Issue 3 (20th May 2015) - Loopstra, Rachel; Tarasuk, Valerie
<x content-type="archive" xml:space="preserve">Abstract</x> This article reflects on the insights afforded by the regular measurement and monitoring of household food insecurity in Canada juxtaposed against information on food bank usage in the population. We show that the number and characteristics of people using food banks suggest that this population is a non-representative subset of the food insecure population. We also highlight how the number of people using food banks is insensitive to the level of household food insecurity in the population. Who goes to food banks is a function of the nature of food bank operations and the severity of food insecurity. Representative data on household food insecurity should be regularly collected and utilised to make policy recommendations for interventions to address the problem of insecure food access.